Stonecat ecology in St. Vrain Creek, CO - D'Amico, Timothy W., author; Winkelman, Dana, advisor; Kendall, William, committee member; Hess, Ann, committee member (Colorado State University. Libraries, 2018)
Stonecat Noturus flavus are a small-bodied native catfish found from southern Canada to the southern United States, and from the Appalachian Mountains to the Rocky Mountains. In Colorado, there are two remaining populations of Stonecat, including one geographically isolated population in St. Vrain Creek, which runs through the Front Range in Longmont, CO. There are five major drainages running through Colorado's Front Range, which is where most of the state's population is concentrated. As such, these streams are highly urbanized. When compared to the other four major Front Range streams, St. Vrain Creek contains a disproportionately high number of native fish species, including Colorado Species of Special Concern such as Stonecats. There has not yet been a quantitative analysis of population demographic parameters or individual habitat selection preferences of Stonecats. I sought to estimate both of these through a mark-recapture study using passive integrated transponder (PIT) tags. There are a number of assumptions associated with mark-recapture studies which I addressed through individual experiments, including tag loss, physical closure and detection probability of known tags. I evaluated tag loss under laboratory conditions. PIT tags were surgically implanted into the peritoneal cavity of Stonecats (n = 157) ranging from 71 mm to 213 mm through an incision closed with a single Braunamid suture and the fish were monitored for 120 weeks. After 120 weeks, there were fifteen lost tags (9.6%) and eight mortalities (5.0%). I evaluated our dataset of individual encounter histories and covariates including time since tagging, fish length and tag type in a multistate model framework using Program MARK. Time since tagging has an inverse effect on tag loss; if fish are going to lose tags, it will be relatively soon post-tagging. Additionally, fish length has a negative effect, with tag loss decreasing with fish length. These results support our assumption that using PIT tags to individually mark Stonecats is an appropriate method, and we now have a better understanding of tag loss rates over a long-term study period. I evaluated population demographic parameters and individual habitat selection preferences of Stonecats in a field experiment. PIT tags were surgically implanted in Stonecats (n = 679) ranging from 70 mm to 230 mm. I monitored tagged Stonecats with both static and mobile PIT antennae. Our results from the static antennae show that the proportion of Stonecat encounters are higher at night and during the summertime. From the mobile PIT antenna results, I determined Stonecats prefer coarse substrate at an intermediate velocity (0.29 m/s) and intermediate depth (0.3 m). Conclusions from this study will be used to inform future urban stream management in conjunction with managing for sensitive fishes such as Stonecats.